Zakat management innovation: Wakalah contract for cash flow stabilization - Muqorobin, Ahmad; Hubur, Aa; Budiman, Alwan Rifqi; Hidayah, Akmal; Yahuza, Bello Sani (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – Zakat institutions (ZIs) face managerial inefficiencies to the extreme seasonality of zakat fitr collection, which restricts distribution to short-term consumptive aid. This study analyzes LAZISMU's "year-round zakat fitr" program implementation at LAZISMU Ponorogo, East Java, as a fiqh-management innovation designed to address this operational challenge by harmonizing Sharia compliance with financial sustainability.Methodology – A qualitative, single-case study design was employed. Data were collected through in-depth interviews with LAZISMU management and Sharia experts, supplemented by analyses of institutional documents and fiqh rulings. An interactive qualitative model was used to examine the legal foundations and managerial implications of the program.Findings – This study finds that Sharia compliance is achieved through the wakalah contract rather than ta'jil (early payment). This legal framework allows for the temporal separation of fund collection from disbursements. Consequently, the institution successfully transforms its cash flow into a stable, continuous flow from a volatile seasonal lump sum, thereby resolving critical operational bottlenecks.Implications – The fiqh-management model enhances strategic planning and operational efficiency. By stabilizing cash flow, ZIs can shift their distribution strategy from purely reactive and consumptive to proactive, enabling the integration of zakat fitr funds into long-term productive empowerment programs without violating Sharia constraints.Originality – Unlike previous studies that predominantly focus on the distributional aspects of wakalah, this study offers a novel analysis of the wakalah contract as a strategic cash flow-smoothing tool in the zakat administration. It bridges classical Islamic jurisprudence with modern corporate finance theory and provides a replicable model for Islamic social finance institutions to overcome operational seasonality.